Determining Water Quality in Urban Drinking Water Networks Using Artificial Intelligence Approaches - Şener, Abdullah; Ergen, Burhan; Mızrak, Hamit (Fırat University, 2022)
Water has vital importance as it provides balance to all living things and keeps their activities alive. The quality of drinking water depends on the chemical, biological, physical and radiological criteria of water. Water quality is a factor that directly affects human health and ecological system. Many techniques and models have been developed to measure the quality of drinking water in urban networks. With the rapid increase in the world population, the number of drinking water networks in vital areas is also increasing. It is a time-consuming process for people to be able to respond to such needs instantly. Recent technological developments are playing an active role in solving such problems. In this study, artificial intelligence-based analyzes were performed on an open data set with water components. The analyzes performed determined whether the water was of good quality. Machine learning methods and ensemble learning algorithms were used in the experimental analysis. The best performance result was obtained using the bagging method. With this method, an overall accuracy of 96.44% was achieved.

Öz: Su, bütün canlıların yaşam dengesini sağlayan ve faaliyetlerini ayakta tutan hayati bir öneme sahiptir. İçme suyunun kalitesi suyun kimyasal, biyolojik, fiziksel ve radyolojik ölçütleriyle bağlantılıdır. Su kalitesi insan sağlığını ve ekolojik sistemi doğrudan etkileyen bir faktördür. Kentsel şebekelerde içme suyunun kalitesini ölçebilmek için birçok teknik ve model geliştirilmiştir. Dünya nüfusunun hızlı artışı ve yaşamsal alanlardaki içme suyu şebekelerinin sayısını da artırmaktadır. Bu tür ihtiyaçlara anlık cevap verebilmek insanlar için zaman alıcı bir süreçtir. Son zamanlardaki teknolojik gelişmeler bu tür problemlerin çözümünde etkin rol üstlenmektedir. Bu çalışmada su bileşenlerini içeren açık veri kümesi kullanılarak yapay zekâ tabanlı analizler gerçekleştirilmiştir. Gerçekleştirilen analizlerde suyun kaliteli olup olmadığı tespit edilmiştir. Deneysel analizlerde makine öğrenme yöntemleri ve topluluk öğrenme algoritmaları kullanılmıştır. En iyi performans sonucu torbalama yöntemi ile elde edilmiştir. Bu yöntem ile %96,44 oranında genel doğruluk başarısı sağlanmıştır.
Kentsel İçme Suyu Şebekelerinde Suyun Kalite Seviyesinin Yapay Zekâ Yaklaşımları Kullanılarak Belirlenmesi